High Rejection Sensitivity in Patients With Somatoform Pain Disorder - Nacak, Yeliz; Morawa, Eva; Erim, Yesim (Frontiers in Psychiatry, 2021)
Objective: Rejection sensitivity (RS) is often associated with mental disorders but as yet has not been investigated in patients with somatoform pain disorder (SPD). The aim of the study was to explore the degree of RS in patients with SPD compared to healthy controls. In addition, we examined factors associated with RS and the moderator effect of SPD. Methods: A total of 65 patients with SPD (confirmed by Structured Clinical Interview, SCID-I) and 65 age- and gender-matched healthy controls participated. Rejection Sensitivity Questionnaire (RSQ), Patient Health Questionnaire (PHQ-9, PHQ-15), Relationship Scale (ReSQ), Essen Trauma Inventory (ETI) and the Childhood Trauma Questionnaire (CTQ) were applied. Multiple linear regression analysis was performed. Results: The level of RS was significantly higher in patients with SPD compared to healthy controls (M = 10.30, SD = 5.64; M = 6.13, SD = 2.50; p < 0.001; d = 0.95). Higher levels of depressive symptoms (p < 0.001), childhood adversities (p < 0.001) and the insecure attachment style (p = 0.007) were related to higher levels of RS. No significant moderation effect was detected. Conclusions: Patients with SPD are highly sensitive to social rejection. In addition, insecure attachment styles as well as depressive symptoms and childhood adversities are strongly associated with RS. Further studies are needed to figure out how RS is connected to SPD over lifetime.
CRIS-Team Scopus Importer:2021-04-19
Keywords: adverse life events; attachment; childhood adversities; chronic pain; rejection sensitivity; somatoform (pain) disorder